Increased asymmetric dimethylarginine and nitric oxide levels in patients with migraine - Uzar, Ertugrul (Springer Milan, 2011)
Asymmetric dimethylarginine (ADMA) has been found as correlated with endothelial dysfunction and oxidative stress. There are few studies regarding ADMA and nitric oxide (NO) levels in patients with migraine and alterations of ADMA and NO levels during migraine attack are not well-known. Therefore, in present study, we aimed to measure NO and ADMA levels in patients with migraine and compare them with the control group to investigate the correlation between migraine, oxidative stress and endothelial dysfunction. The migraine group consisted of 59 patients, including 22 suffering from migraine with aura and 37 suffering from migraine without aura. The control group consisted of 31 healthy volunteers without headache. The patients in migraine group were divided into subgroups based on whether attack period was present or not and whether it was migraine with or without aura. Plasma ADMA levels were measured using an enzyme-linked immunosorbent assay method. Migraine patients had higher concentrations of NO (35.6 ± 7.7, 31.0 ± 6.2 μmol/L, respectively, p = 0.005) and ADMA (0.409 ± 0.028, 0.381 ± 0.044 μmol/L, respectively, p = 0.001) levels when compared with the healthy controls. During migraine attack, NO and ADMA levels were found to be significantly higher in migraine group as compared to control group (respectively, p = 0.015, p = 0.014). Similarly, NO and ADMA levels in the patients with migraine in the interictal period were found to be significantly higher as compared to control group (p = 0.011, p = 0.003). In conclusion, higher ADMA and NO levels of patients with migraine supported that oxidative stress and endothelial dysfunction may have a role in migraine pathogenesis.